The Influence of the Application of Information Technology on Student Performance in Academic Activities at Indonesian Higher Education Institutions - Gilang Ramadhan Manik; Andini Nur Bahri (JOURNAL SAINS STUDENT RESEARCH, 2025)
The development of information technology has significantly transformed higher education, particularly in facilitating access to information, academic communication, and online learning systems. This study aims to examine the influence of information technology implementation on student academic performance in Indonesian universities. Using a quantitative approach with a correlational survey method, data were collected from 47 student respondents through a Likert-scale questionnaire. The analysis techniques applied were simple linear regression and partial t-test using SPSS version 29. The results showed that the application of information technology had a positive and significant effect on student performance, with a coefficient of determination (R2) of 0.679 and t-test significance value of < 0.001. these findings confirm that optimal utilization of technology can enhance the effectiveness and quality of students’ academic outcomes. Therefore, higher education institutions are encouraged to strengthen digital literacy and technology infrastructure as part of their strategy to improve learning quality.